2020
DOI: 10.1038/s41598-020-65895-0
|View full text |Cite
|
Sign up to set email alerts
|

Soluble programmed death-ligand 1 rather than PD-L1 on tumor cells effectively predicts metastasis and prognosis in soft tissue sarcomas

Abstract: The soluble form of PD-L1 (sPD-L1) is related to a poor prognosis in various cancers. Comparisons of sPD-L1 and PD-L1 expressed on tumor cells in soft tissue tumor patients have not been reported. The purpose of this study was to analyze serum sPD-L1 and PD-L1 levels in soft tissue tumor patients. A total of 135 patients with primary soft tissue tumors were enrolled in this study. The sPD-L1 level was quantitatively measured by enzyme immunoassay, and PD-L1 expression on high grade sarcoma cells was analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Our data showed that 19 of 21 cervical cancer patients had sPD‐L1 levels above the mean of the controls. sPD‐L1 levels have been increased in different types of cancer and are associated with disease severity and prognosis [13,60,61]. It is also possible that the presence of sPD‐L1 may indicate patients who would not respond well to some forms of PD‐L1 blockade antibody therapy, as it has been reported that secreted PD‐L1 variants can mediate resistance to PD‐L1 blockade by acting as a decoy [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that 19 of 21 cervical cancer patients had sPD‐L1 levels above the mean of the controls. sPD‐L1 levels have been increased in different types of cancer and are associated with disease severity and prognosis [13,60,61]. It is also possible that the presence of sPD‐L1 may indicate patients who would not respond well to some forms of PD‐L1 blockade antibody therapy, as it has been reported that secreted PD‐L1 variants can mediate resistance to PD‐L1 blockade by acting as a decoy [10].…”
Section: Discussionmentioning
confidence: 99%
“…The over‐expression of PD‐L1 in tumor tissues has been considered as a predictive biomarker; however, some authors have concluded that this molecule may not be a robust indicator of treatment response due to the fact that PD‐L1‐negative tumors can also respond to PD‐1/PD‐L1 targeting [11,12]. The soluble form of PD‐L1 (sPD‐L1) has been reported to be an improved predictor of metastasis versus membrane‐bound PD‐L1 and a prognostic factor for the survival of first‐line chemotherapy, and may also mediate resistance to PD‐L1 blockade [13‐16].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 31 studies involving 17 tumors and a total of 3,780 patients met our inclusion criteria ( Figure 1 ). The tumor types included in the study were; Nasopharyngeal Carcinoma ( 11 ), Cholangiocarcinoma ( 12 ), lung cancer ( 9 , 10 , 13 17 ), Hepatocellular carcinoma ( 20 , 21 , 39 , 40 ), Thyroid carcinoma ( 22 ), Mesothelioma ( 23 ), Colorectal carcinoma ( 24 , 25 ), NK/T cell lymphoma ( 26 , 27 ), Peripheral T-cell lymphoma ( 28 ), Large B-Cell lymphoma ( 29 , 35 ), Hodgkin lymphoma ( 31 ), Ovarian carcinoma ( 32 ), Soft tissue sarcomas ( 33 ), Renal cell carcinoma ( 7 ), Esophageal carcinoma ( 34 ), Gastric carcinoma ( 4 , 35 ), and Pancreatic adenocarcinoma ( 36 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…In gastric cancer, although serum sPD-L1 levels showed a trend of elevation in patients with high tissue PD-L1 expression, a statistically significance was not observed ( 20 ). A recent study performed in soft tissue sarcomas also revealed that there were no obvious differences in sPD-L1 levels between tissue PD-L1 positive group and PD-L1 negative group ( 35 ). One possible explanation is the mPD-L1 expression may vary within the same tumor spatially and temporally.…”
Section: Discussionmentioning
confidence: 96%